EFFICACY OF MYCORRHIZAE AND Trichoderma AS A BIOLOGICAL CONTROL OF BASAL STEM ROT DISEASE (Ganoderma) AND AS A PROMOTOR OF OIL PALM SEEDLING GROWTH - Donnarina Simanjuntak; Fahridayanti Fahridayanti; Agus Susanto (Widyariset, 2013)
The experiment was in randomized block design which consisted of 14 treatments with 7 treatment combinations with Ganoderma infection and 7 treatment combinations without Ganoderma infections, there were 75 replications for each treatment combinations. The treatment combinations included applications of Mycorrhizae, Trichoderma, and standard fertilizer. Variables observed were disease incidence of Ganoderma, plant height, number of frond, and weight mass. The results showed that the application of Mycorrhizae was able to control basal stem rot disease until 7 months after the application of Ganoderma. A single application of Mycorrhizae had not been able to promote seedlings growth until 10 months. The role of Mycorrhizae in promoting seedling growth until 10 months was demonstrated when combined with Trichoderma and standard fertilizer application.